(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Although it is mostly used in Medicine, the placebo effect has been exploited in Marketing as well, in recent years. In Medicine, the placebo effect is defined as the improving state of a patient as a result of administering a simulated treatment, without any therapeutic healing effect. The current paper presents the results obtained in the studies that tested the placebo effect in marketing, and the conclusions of an experiment in which the possibility of producing the placebo effect on the consumer when the country of origin of an identical product differs was tested.